The freedom of alienated reflexive subjectivity in The Stanley Parable. (February 2020) - Zhu, Feng
The Stanley Parable (Galactic Cafe, 2013) is a game that self-reflexively meditates on the relationship between the structure in which choices are presented to the player in first-person exploration games and contemporary concerns over freedom. It takes, as its subject matter, its own 'variable expressiveness', yet must also delimit that expressiveness in order to direct the player towards a self-reflexive mindset. The article proposes, by analysing three of the endings in the game, that this endeavour necessitates the game to compromise its 'gameness' and to move towards being a Lukácsian novel caught in an endless interiority; it must maintain a tension between giving the player freedom and room for expression, on the one hand, and being tightly focused on reflections concerning freedom and meaning, on the other. This reveals something about what computer games must sacrifice in order to grasp at meaning and also what would be required for a work to indicate that in which freedom consists. It will be argued that neither of the two kinds of subjectivity that are detailed by Lukács ((1971) The Theory of the Novel . Cambridge, Massachusetts: MIT Press) – the Homeric subject without interiority and the alienated modern subject on a Sisyphean quest for meaning – are compatible with freedom. Instead, the carefully conceived tensions to which The Stanley Parable gives rise initiates a 'dance' that gestures towards freedom inhering in a subjectivity which avoids these possibilities. This could only be accomplished by being more than both a game and a novel. The implications bear upon the form of a medium that can most suitably function as a homology for the aforementioned subjectivity that transcends the two Lukácsian poles.